Bilingual Learning Management for Mathematics Lesson atRSBI SMP Negeri 1 Magelang - Kustomo, Kustomo (2011)
The objectives of this research are to describe (1) characteristics of the planning of bilingual learning in mathematics lesson at SMP N 1 Magelang. (2) characteristics of the implementation of bilingual learning in mathematics lesson at SMP N 1 Magelang. (3) characteristics of the evaluation of bilingual learning in mathematics lesson at SMP N 1 Magelang. This research is a qualitative research using ethnography design. This research is conducted at SMPN 1 Magelang. The main subject of this research is the principal, teachers and students in SMPN 1 Magelang environtment. Data collection method uses interview, observation, and documentation. Data analysis is started from (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Data validity test uses credibility, transferability, confirmability and dependability. The result of this research are (1) the planning conducted in bilingual mathematics learning at SMPN 1 Magelang is to plan lesson plan, instructional media, tesselation and estimation material, time of learning, and bridging course program for new students. The mathematics teachers of SMPN 1 Magelang still find some constraints in preparing lesson plan, so the school provides Mathematics-English Dictionary and asks them to ask the English teacher when preparing the lesson plan that is used to bilingual learning in mathematics lesson. (2) Bilingual learning in mathematics lesson at SMPN 1 Magelang is conducted using some materials in English, and also presented by learning-based ICT. However, in the learning implementation, the teachers and students have not been optimal in mastering the material in English and using innovative method. The school invites some lectures from outside of the school to give guidance and hold English quick course program, training conversation, and also workshop for students and teachers. (3) The evaluation of a bilingual learning in mathematics lesson at SMPN 1 Magelang is conducted three times namely daily test, midterm test, and final test. The exercise is using English that includes aspects of cognitive, affective, and psychomotor. The teachers prepare evaluation report which contains of students score analysis and learning difficulties. The students who get score under KKM join a remedial program held by the school.